76.7.12 problem 12

Internal problem ID [17485]
Book : Differential equations. An introduction to modern methods and applications. James Brannan, William E. Boyce. Third edition. Wiley 2015
Section : Chapter 3. Systems of two first order equations. Section 3.3 (Homogeneous linear systems with constant coefficients). Problems at page 165
Problem number : 12
Date solved : Tuesday, January 28, 2025 at 10:39:23 AM
CAS classification : system_of_ODEs

\begin{align*} \frac {d}{d t}x \left (t \right )&=3 x \left (t \right )+6 y \left (t \right )\\ \frac {d}{d t}y \left (t \right )&=-x \left (t \right )-2 y \left (t \right ) \end{align*}

Solution by Maple

Time used: 0.066 (sec). Leaf size: 22

dsolve([diff(x(t),t)=3*x(t)+6*y(t),diff(y(t),t)=-x(t)-2*y(t)],singsol=all)
 
\begin{align*} x \left (t \right ) &= c_{1} +c_{2} {\mathrm e}^{t} \\ y \left (t \right ) &= -\frac {c_{2} {\mathrm e}^{t}}{3}-\frac {c_{1}}{2} \\ \end{align*}

Solution by Mathematica

Time used: 0.002 (sec). Leaf size: 48

DSolve[{D[x[t],t]==3*x[t]+6*y[t],D[y[t],t]==-x[t]-2*y[t]},{x[t],y[t]},t,IncludeSingularSolutions -> True]
 
\begin{align*} x(t)\to c_1 \left (3 e^t-2\right )+6 c_2 \left (e^t-1\right ) \\ y(t)\to c_2 \left (3-2 e^t\right )-c_1 \left (e^t-1\right ) \\ \end{align*}